2021
DOI: 10.1021/acs.iecr.1c01961
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Economic Analysis of the Hydrothermal Reduction of CO2 into Formate

Abstract: In this work, the mass and energy balances and the economic analysis of a continuous process for the reduction of CO 2 (captured as NaHCO 3 ) into sodium formate using Zn as the reductant are studied. The reaction in hydrothermal media has the advantage of easily integrating the conversion system with the CO 2 capture process by absorption in basic solutions. The process conditions (pressure, Zn/NaHCO 3 molar ratio, and residence time) were theoretically optimized. A reaction temperature of 275 °C was selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(97 reference statements)
1
1
0
Order By: Relevance
“…The addition of NaHCO 3 to the reaction led to a significantly higher production of formic, acetic, and, particularly, lactic acid. It can be expected that a fraction of the FA produced was formed from bicarbonate reduction, as observed in previous works with model compounds and algae, in which experiments using NaH 13 CO 3 demonstrated by NMR analysis that up to 80% of FA was produced by CO 2 conversion and the remaining proportion originated from biomass decomposition. ,, In a previous work of the authors using glucose as a model compound of the hydrothermal decomposition of the cellulose fraction of biomass and tracking the conversion of inorganic NaH 13 CO 3 by NMR, it was found that under the experimental conditions considered in this work (250 °C, NaHCO 3 inorganic carbon source), 30% of the produced formic acid originated from the inorganic carbon source and the remaining amount was produced from glucose. The enhancement in the production of AA and LA by addition of NaHCO 3 can be assigned to a change in the reactive environment and particularly the higher pH.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The addition of NaHCO 3 to the reaction led to a significantly higher production of formic, acetic, and, particularly, lactic acid. It can be expected that a fraction of the FA produced was formed from bicarbonate reduction, as observed in previous works with model compounds and algae, in which experiments using NaH 13 CO 3 demonstrated by NMR analysis that up to 80% of FA was produced by CO 2 conversion and the remaining proportion originated from biomass decomposition. ,, In a previous work of the authors using glucose as a model compound of the hydrothermal decomposition of the cellulose fraction of biomass and tracking the conversion of inorganic NaH 13 CO 3 by NMR, it was found that under the experimental conditions considered in this work (250 °C, NaHCO 3 inorganic carbon source), 30% of the produced formic acid originated from the inorganic carbon source and the remaining amount was produced from glucose. The enhancement in the production of AA and LA by addition of NaHCO 3 can be assigned to a change in the reactive environment and particularly the higher pH.…”
Section: Resultssupporting
confidence: 78%
“…These previous works with model organic substances have demonstrated the technical feasibility of the process, but in order to design a competitive and economic process of FA production, the reagents and feedstock costs should represent a minor fraction of the total disbursement of the process. Indeed, in a previous work of the authors in which an economic analysis of the hydrothermal conversion process is presented, considering a metal instead of biomass derivatives as a reductant, it was concluded that the reductant amounted for more than 50% of the production costs; 11 therefore, the substitution of the expensive metal reductant by an inexpensive and renewable reductant such as organics derived from the liquefaction of biomass would greatly contribute to the economic feasibility of the process. Thus, the next required step is using lignocellulosic biomass directly as a reductant as it is a globally available, sustainable, and inexpensive feedstock, which can be obtained from other industries as their residues.…”
Section: Introductionmentioning
confidence: 99%